2011
DOI: 10.1177/0960327111407230
|View full text |Cite
|
Sign up to set email alerts
|

Narrowing of airway caused by ingestion of methyl ethyl ketone peroxide

Abstract: Although ingestion of methyl ethyl ketone peroxide (MEKP) is rare, it carries a high risk of morbidity and mortality. This paper reports the first such case from Turkey in which a 70-year-old man unintentionally ingested MEKP in his kitchen. The patient was brought into the emergency department (ED) within 1 hour of ingestion, with the symptoms of sore throat, shortness of breath, nausea and vomiting. Visual examination of the oropharynx revealed minor burns and uvular edema. A laryngoscope examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…We considered explorative surgery at this point, but it was cancelled because the patient’s vital signs had been worsening rapidly. Additionally, prednisolone should be given to treat airway edema [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…We considered explorative surgery at this point, but it was cancelled because the patient’s vital signs had been worsening rapidly. Additionally, prednisolone should be given to treat airway edema [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…If inhaled, severe chemical pneumonitis tends to occur. MEKP can be aspirated resulting in proximal airway edema and obstruction, pneumonitis, and acute respiratory distress syndrome [7]. Our patient too had acute respiratory failure attributable to radiologically confirmed chemical pneumonitis.…”
Section: Discussionmentioning
confidence: 68%
“…A similar case is observed in a 19 year old woman who intentionally ingested glutaraldehyde, commonly used as a sanitizer. This woman after 10 hours from the ingestion of the chemical, exhibited metabolic acidosis and respiratory distress, required hospitalization in intensive care and an endotracheal intubation due to the swelling of the larynx (18,19). The patients in our study showed high rates of respiratory complications and side-effects probably due to the fact that the substance was intentionally ingested as attempt for suicide.…”
Section: Discussionmentioning
confidence: 80%